2011
DOI: 10.2134/jeq2010.0403
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of Vinyl Chloride in Aquifer Microcosms

Abstract: The anaerobic degradation potential at a chloroethene-contaminated site was investigated by operating two anoxic column aquifer microcosms enriched in iron(III). One column was fed with vinyl chloride (VC) only (column A) and one with VC and acetate (column B). In column A, after about 600 pore volume exchanges (PVEs), VC started to disappear and reached almost zero VC recovery in the effluent after 1000 PVEs. No formation of ethene was observed. In column B, effluent VC was almost always only a fraction of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…sulfate-reducing, Chapelle, 1996). Finally, while anaerobic oxidation was suggested as a possible degradation pathway (Smits et al, 2011), the likeliness of such a process to occur remains unclear. Gossett et al previously suggested that what was in microcosms thought to be anaerobic oxidation might actually be aerobic oxidation with O 2 concentrations so low that O 2 is quickly consumed and not measurable (Gossett, 2010).…”
Section: Chlorinated Ethene C and Cl Isotopic Compositionmentioning
confidence: 99%
“…sulfate-reducing, Chapelle, 1996). Finally, while anaerobic oxidation was suggested as a possible degradation pathway (Smits et al, 2011), the likeliness of such a process to occur remains unclear. Gossett et al previously suggested that what was in microcosms thought to be anaerobic oxidation might actually be aerobic oxidation with O 2 concentrations so low that O 2 is quickly consumed and not measurable (Gossett, 2010).…”
Section: Chlorinated Ethene C and Cl Isotopic Compositionmentioning
confidence: 99%
“…Non-detection of the VC reductase genes does not necessarily indicate that VC reduction does not occur, as lower chlorinated ethene concentrations in total would provide fewer electron acceptors for this bacterial guild, and thus these bacteria would be present in smaller quantities and are possibly below detection. It is also possible that VC respiration in this part of the plume is facilitated by currently unidentified species or genes or by microaerophilic or anaerobic oxidation (Bradley et al, 1998;Liang et al, 2017;Smits et al, 2011).…”
Section: Degradation Mechanisms / Summarymentioning
confidence: 99%
“…This discovery has shifted the paradigm that complete biotic degradation of chlorinated ethenes is only possible when Dehalococcoides is a main player in a groundwater microbial community. Further, it is also possible for cDCE and VC to be degraded by microbial oxidation, including microaerophilic oxidation, cometabolic oxidation by methanotrophs and etheneotrophs, or anaerobic oxidation (Bradley et al, 1998;Bradley and Chapelle, 2000;Liang et al, 2017;Smits et al, 2011). Chlorinated ethene degradation may also proceed abiotically in ironand sulfate-reducing conditions when mediated by reactive iron minerals such as iron sulfides, magnetite, and green rust (He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%